Common Infections and Antibiotic Prescribing during the First Year of the COVID-19 Pandemic: A Primary Care-Based Observational Cohort Study - Josi A. Boeijen; Alike W. van der Velden; Saskia Hullegie; Tamara N. Platteel; Dorien L. M. Zwart; Roger A. M. J. Damoiseaux; Roderick P. Venekamp; Alma C. van de Pol (MDPI AG, 2021)
Presentation and antibiotic prescribing for common infectious disease episodes decreased substantially during the first COVID-19 pandemic wave in Dutch general practice. We set out to determine the course of these variables during the first pandemic year. We conducted a retrospective observational cohort study using routine health care data from the Julius General Practitioners' Network. All patients registered in the pre-pandemic year (n = 425,129) and/or during the first pandemic year (n = 432,122) were included. Relative risks for the number of infectious disease episodes (respiratory tract/ear, urinary tract, gastrointestinal, and skin), in total and those treated with antibiotics, and proportions of episodes treated with antibiotics (prescription rates) were calculated. Compared to the pre-pandemic year, primary care presentation for common infections remained lower during the full first pandemic year (RR, 0.77; CI, 0.76-0.78), mainly attributed to a sustained decline in respiratory tract/ear and gastrointestinal infection episodes. Presentation for urinary tract and skin infection episodes declined during the first wave, but returned to pre-pandemic levels during the second and start of the third wave. Antibiotic prescription rates were lower during the full first pandemic year (24%) as compared to the pre-pandemic year (28%), mainly attributed to a 10% lower prescription rate for respiratory tract/ear infections; the latter was not accompanied by an increase in complications. The decline in primary care presentation for common infections during the full first COVID-19 pandemic year, together with lower prescription rates for respiratory tract/ear infections, resulted in a substantial reduction in antibiotic prescribing in Dutch primary care.